Remediation Technology for Heavy Metal-Contaminated Soil on Copper Post- Mining Land Reclamation (Jurnal Pengelolaan Lingkungan Pertambangan, 2024)
Indonesia is a country with very high mineral reserves. Copper is one of the most important minerals found and produced in Indonesia. According to data from USGS in 2023, Indonesia is the world's seventh-largest copper producer. Copper mining activities primarily utilize open-pit mining techniques compared to underground mining techniques. Open-pit mining techniques lead to environmental damage, including land degradation, erosion, deforestation, ecosystem destruction, and soil, air, and water pollution due to acid mine drainage. The aim of this research is to provide remediation technologies recommendations for heavy metal-contaminated soil on copper post-mining land. Mine reclamation plays a crucial role in addressing various issues on post-mining lands. Waste dump area is one of the focus areas in reclamation activities that used as a place to store non-valuable materials. Waste dump area typically contain heavy metals that are harmful to the environment. High concentrations of heavy metals in the soil can make it toxic, which then has an impact on reducing soil quality and poisoning plants. Selecting suitable ameliorants and hyperaccumulator plants that are capable to reduce heavy metal toxicity is the key to successful mine reclamation. Zeolite ameliorant can reduce heavy metal content in the soil by increasing adsorption complexes, while dolomite can reduce heavy metal content in the soil by increasing soil pH. Phytoremediation by using hyperaccumulator plants also can reduce soil toxicity through destruction, inactivation, or immobilization of heavy metals into harmless forms.